“Helping girls and young women grow into confident, self-respecting, responsible community members” : a case study of Girl Guides Australia - Lalor, Jennifer Ann (Curtin University, 2011)
The public perception of Girl Guides is often one of a staid and conservative organisation of ‘good’ girls, who perform community service and tie knots, and adult members who are straight-laced and slightly boring, but willing helpers. This study examined whether these perceptions are justified or whether the programs of Girl Guides Australia follow the principles of non-formal education, as claimed by the organisation, and provide its members with opportunities that are useful in today’s world. Specifically, this research explored the perceptions of: the Australian Guide Program by youth members (N=437) and their parents (N=434); the Australian Adult Leadership Program for Leaders of those youth members (N=438); and the Australian Trainers’ Training Program for Trainers of those Leaders (N=67).Quantitative data were collected from four groups – youth members, their parents, Leaders and Trainers – through the use of questionnaires which were structured to gather similar information for each program using age-appropriate language. Three adult-member focus-group discussions were also held to provide background information regarding the motivation of participants holding a leadership position in Guides. Using the statistical package PASW Statistics (also known as SPSS), data for each group were analysed separately, and comparisons were made of the perceptions of different youth member age groups. Differences between the four participant groups were also examined where appropriate. The qualitative focusgroup data were analysed manually.Results showed that all groups identified the use of non-formal education principles, such as learning by doing, mentoring, shared decision-making, having well-trained leaders, being voluntary in nature, providing a personal challenge and practical skill based learning, being self-paced, involving age-appropriate non-competitive activities, facilitating teamwork and providing leadership skill development. The groups also recognised the educational nature of the programs and reported a wide range of practical and personal skills that had been learned. Youth members and parents reported that participation in the program had helped Guides to become more self-confident, self-respecting and responsible. All groups perceived that participation in the programs had helped with school / study, socially and in the workforce. Parents appreciated the non-competitive, safe and girl-only environment where their daughters could have fun. Data showed that Leaders delivered the youth program in a developmentally-appropriate way in which increasing autonomy was given to Guides as they got older. Trainers and Leaders agreed that participation in their respective programs had extended their skills and prepared them for their roles in Guiding. The focus groups identified the intangible ‘Guiding Spirit’ as binding everyone together and helping to reinforce the willingness to volunteer time and effort for the benefit of all Guide members.In summary, the study has shown that the programs provided by Girl Guides Australia were considered to follow the principles of non-formal education for the benefit of youth and adult members in terms of practical skill development, leadership opportunities, fun, friendship and personal development. Participation in the programs provided by Girl Guides Australia satisfies the organisation’s mission of: ... helping girls and [young] women grow into confident, self-respecting, responsible community members.